2023
DOI: 10.3390/su152014707
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sustainability Reporting on Financial Performance: Evidence from Turkish FBT and TCL Sectors

Serhii Lehenchuk,
Iryna Zhyhlei,
Olena Ivashko
et al.

Abstract: This study investigated the impact of sustainability reporting on financial performance, with a focus on companies in the Turkish food, beverage and tobacco and textile, wearing apparel and leather sectors. The sustainability reports of 48 companies listed on the Istanbul Stock Exchange for 2022 were studied, and the quality of sustainability practices was determined by using a general index (Sustainability Reporting Disclosure Quality Index (SRDQI)) and three partial indices (Environmental Disclosure Quality … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…The study emphasis that there is an interconnected link among the sustainable practice and the firm's financial performance. Another current study by Lehenchuk et al (2023) conducted on sustainability reporting in the Turkish FBT and TCL sectors revealed that there was no statistically significant effect of the overall quality of sustainability reporting on financial performance measures, with the exception of a positive correlation between the Corporate Governance Disclosure Quality Index and the Asset Turnover Ratio. In their study, Santis et al (2016) employed the sustainability index within the framework of the Triple Bottom Line (TBL) to examine the correlation between financial performance (FP) and sustainability in Brazilian public companies from 2009 to 2013.…”
Section: Introductionmentioning
confidence: 64%
“…The study emphasis that there is an interconnected link among the sustainable practice and the firm's financial performance. Another current study by Lehenchuk et al (2023) conducted on sustainability reporting in the Turkish FBT and TCL sectors revealed that there was no statistically significant effect of the overall quality of sustainability reporting on financial performance measures, with the exception of a positive correlation between the Corporate Governance Disclosure Quality Index and the Asset Turnover Ratio. In their study, Santis et al (2016) employed the sustainability index within the framework of the Triple Bottom Line (TBL) to examine the correlation between financial performance (FP) and sustainability in Brazilian public companies from 2009 to 2013.…”
Section: Introductionmentioning
confidence: 64%
“…Namun, karakteristik perusahaan seperti ukuran, usia, jenis industri, dan struktur modal ditemukan mempengaruhi kinerja keuangan perusahaan dengan cara yang berbeda -beda. (Lehenchuk et al, 2023).…”
Section: Sustainability Finance (Keuangan Berkelanjutan)unclassified
“…Beberapa studi telah menyoroti pentingnya pengungkapan keberlanjutan di sektor keuangan maupun non keuangan. Misalnya, sebuah tinjauan (Herbohn et al, 2014), (Lehenchuk et al, 2023) dan (Remo-Diez et al, 2023) menegaskan dampak positif dari pelaporan keberlanjutan yang kuat terhadap kinerja keuangan perusahaan dan kepercayaan pemangku kepentingan. Serupa dengan itu, (Yadegaridehkordi et al, 2023) menemukan bahwa faktor -faktor kunci seperti orientasi kewirausahaan hijau, inovasi hijau, komitmen kepemimpinan, tekanan pemangku kepentingan, dan orientasi pasar sebagai faktor penentu yang signifikan dari tiga pilar (lingkungan, keuangan, dan sosial) kinerja berkelanjutan di UKM manufaktur Malaysia.…”
unclassified
“…Due to the ever-increasing awareness of ethical and sustainable business practices, organisations are pressured to connect their business practices and strategies to impacts on the environment, society and stakeholders they interact with [3]. The European Sustainability Reporting Standards [4] specify the information an organisation should disclose about such material impacts, as well as the risks and opportunities concerning environmental, social and governance sustainability matters the company faces.…”
Section: Introductionmentioning
confidence: 99%